Social media usage: Analyzing its effect on academic performance and engagement of higher education students. (April 2023) - Shafiq, Muhammad; Parveen, Khalida
Abstract: In many nations, including Pakistan, students in higher education use social media as a common means of communication. Even while research suggests that using social media in a classroom setting would probably improve students' academic performance, the mechanism underlying this link has not yet been fully investigated. Based on the assertions that integrating social media use is intended to increase student involvement, the purpose of this study was to examine how college students use social media and determine whether social media use has any impact on their academic performance. There are two phases to this study project. Phase I of the data collection process begins with the Top 10 universities in Pakistan being chosen at random. A structured questionnaire was used to gather data from 234 sample respondents, including social media users and non-users, in order to accomplish the study's goals. The findings show that when students use social media's knowledge-sharing capabilities, their academic performance improves. Also, the learning outcome of students who engaged in the social media facilities is more; various aspects discussed in the study revolving around social media are useful for the students, teachers, and educational institutions to enhance their academic purposes. Highlights: In this research work, an empirical study is undergone to gather information about thefeatures of social media. The data has been collected from the 234 respondents with a set of 45 questions. The collected data were analyzed via SEM, F-test, Descriptive statistics and correlationanalysis.